Associations between childhood hearing loss and behavioural and academic difficulties: A Danish cohort study. (November 2016) - Niclasen, Janni; Obel, Carsten; Guldager, Christian; Pleinert, Simone; Dammeyer, Jesper
Abstract: Objective: Negative associations between hearing loss (HL) and behavioural and academic difficulties have been reported. However, most studies are based on small clinical samples. The aim of the present study was to investigate such associations using data from a large-scale non-clinical Danish birth cohort controlling for a large number of relevant confounding factors. Methods: The study applied data from the Aarhus Birth Cohort's 10-12-year-old follow-up (N = 7599). Associations between parent-reported HL on the one hand, and parent- and teacher-reported behavioural difficulties measured by the Strengths and Difficulties Questionnaire (SDQ) and parent-reported academic difficulties on the other hand, were investigated. Results: After controlling for relevant confounding factors, significant associations were observed between parent-reported HL and parent- and teacher-reported Externalising scores, and academic difficulties. Conclusions: Childhood HL is associated with behavioural and academic difficulties. Parent reported HL in a non-clinical cohort is indicative for academic and behavioural difficulties.